Malay Apostates in Malaysia: A Study on Reasons - Morgan, Santhira; Sulong, Jasni (European Publisher, 2019)
The Malaysian Constitution guarantees Freedom of Religion under article 11. Yet, it is tacitly understood that this does not apply to Malay Muslims. In fact, some Malay Muslims have openly declared their apostasy over the Internet. The Malay community does not take Malay apostasy lightly. They show animosity towards anyone who leaves Islam. This research aims to find out the reasons for apostasy and if one can leave Islam against the hadith which calls for the death penalty for apostates. Islam defines an apostate as one who says, does, or believes that Allah and Messenger are not what they claim to be. It looks at the position taken by the Malaysian courts in dealing with apostates. This study uses qualitative methodology and content analysis by evaluating text, social media and interviews with apostates. Many Malays have left Islam to embrace Christianity and Atheism. Many researchers in the past have said that the main cause of apostasy had been the lack of religious knowledge among the Malays. However, this study has found that many of the apostates are well grounded in Islamic studies and some of them have even studied Usuluddin and Figh until university level. Most of the apostates have undergone at least 10-12 years of religious studies in Malaysian school. The results of this study are intended to provide guidance and set examples to the public and the authorities in dealing with apostasy especially among young educated Malays.